2008
DOI: 10.1007/s00340-008-3250-9
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching microscopy with standard fluorophores

Abstract: We introduce far-field subdiffraction-resolution fluorescence imaging based on photoswitching of individual standard fluorophores in air-saturated solution. Here, photoswitching microscopy relies on the light-induced switching of organic fluorophores (ATTO 655 and ATTO 680) into long-lived metastable dark states and spontaneous repopulation of the fluorescent state. In the presence of low concentrations (2-10 mM) of reducing, thiol-containing compounds such as ß-mercaptoethylamine or glutathione, the density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 42 publications
3
85
1
2
Order By: Relevance
“…12, 13, and 15. Cells were prebleached for approximately 5 s to push a large proportion of fluorophores into the dark state (13,15) using only the red laser. Image sequences were then acquired, streamed to disk, and analyzed in real time using custom software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12, 13, and 15. Cells were prebleached for approximately 5 s to push a large proportion of fluorophores into the dark state (13,15) using only the red laser. Image sequences were then acquired, streamed to disk, and analyzed in real time using custom software.…”
Section: Methodsmentioning
confidence: 99%
“…The development of imaging techniques based on the time-multiplexed observation of single fluorescent molecules allows high-contrast fluorescence imaging with a resolution limited only by signal to noise (10)(11)(12). Using standard fluorochromes (13)(14)(15) we have used this approach to investigate the distribution of peripheral RyRs with a resolution of approximately 30 nm. Quantitative analysis of our data shows that the size and morphology of RyR clusters in peripheral couplings is quite different from that deduced by previous studies.…”
mentioning
confidence: 99%
“…Thus, it is required that at any moment, most molecules are prepared in a dark state. Recently, it has been demonstrated that simply blinking of molecules, e.g., because of triplet formation, can be used, which drastically expands the range of usable fluorescent labels (24,25,38). Thus far, however, this blinking required oxygen removal (24,25,39), and the on-counts and off-times were poorly defined, although they determine the obtainable temporal and spatial resolution (25).…”
Section: [1]mentioning
confidence: 99%
“…For SELM on Klarite and nanovoid surfaces, image stacks of 3000 to 10000 frames with 20 ms integration time each were acquired. Strikingly, we observed very strong fluorescence blinking of the dye in the absence of any external agent such as a 'switching buffer', which is typically used in stochastic optical reconstruction microscopy [17] . A static gold background was removed effectively with a subtraction algorithm calculating a slowly converging median for improved localisation.…”
mentioning
confidence: 91%